PERBEDAAN TINGKAT KONSENTRASI SEBELUM DAN SESUDAH ADANYA BISING AKIBAT AKTIFITAS PERLINTASAN KERETA API PADA SISWA DI SEKOLAH DASAR NEGERI 067240 KECAMATAN MEDAN TEMBUNG KOTA MEDAN TAHUN 2015 - irma damayanti; indra chahaya; taufik ashar (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACTDiscomfort can occur in the environment of school, one of them is thenoise. Noise that occurs when subjects ongoing impact on the learning process,which is one of the disruption of the concentration of students. The research wasconducted at the State Primary School 067240 Medan Tembung District whichaims to find out the difference in the level of concentration towards the studentsbefore and after the noise due to railway crossings.This method of this research is pre-experimental design by using onegroup and pre-test post-test. The sample of this research is also using purposivesampling technique which consists of 58 students. The level of noise wasmeasured by using a Sound Level Meter and level of concentration of studentswas measured using a Stroop Test. Data analysis is using non-parametricstatistical tests (Wilcoxon tes t) and Parametric Test (paired t-test) at the 95%significance level.The results showed that in general the average noise level in theclassroom before and while the train passed the railway crossing exceeds thequality standards that have been established in the amount of 55 dB. Other resultsalso showed that the results of interference score of students before the railroadcrossing with a mean of 13,59 and after the railway crossing at 17,40. Thisindicates that the concentration of students has decreased when compared withpretest posttest. Based on the test results of wilcoxon test is known, there are thedifferences in the level of concentration towards the students before and after thenoise due to railway crossing (p. = 0,001).Based on the results of this research are expected to the school in order toreduce the noise while is coming from the rail traffic. Such as the installation ofblind or curtain on the window class, the use of firm window on the outside walltowards the class which is passing of the train tracks, and the use of noisedampening vegetation.Keywords: The level of the noise, Concentration of the students, Stroop Test,Sound Level Meter